2015
DOI: 10.1371/journal.pone.0125208
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Open Data Policies on Consent to Participate in Human Subjects Research: Discrepancies between Participant Action and Reported Concerns

Abstract: Research outlets are increasingly adopting open data policies as a requisite for publication, including studies with human subjects data. We investigated whether open data policies influence participants’ rate of consent by randomly assigning participants to view consent forms with and without discussion of open data policies. No participants declined to participate, regardless of condition, nor did rates of drop-out vs. completion vary between conditions. Furthermore, no significant change in potential consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…• When soliciting informed consent, participants must be made conspicuously aware of their data will be shared. Cummings et al (2015) found that participants were not less likely to consent to research in which their data were to be shared openly, although participants shared common concerns over confidentiality and data security (as well as common inattentiveness patterns with the consent procedure). During consent procedures, one consideration could be to discuss with participants what data will be shared, and perhaps even show them these data (e.g., a sample file prior to the study starting or even their actual data).…”
Section: Sharing For Confidentialitymentioning
confidence: 96%
“…• When soliciting informed consent, participants must be made conspicuously aware of their data will be shared. Cummings et al (2015) found that participants were not less likely to consent to research in which their data were to be shared openly, although participants shared common concerns over confidentiality and data security (as well as common inattentiveness patterns with the consent procedure). During consent procedures, one consideration could be to discuss with participants what data will be shared, and perhaps even show them these data (e.g., a sample file prior to the study starting or even their actual data).…”
Section: Sharing For Confidentialitymentioning
confidence: 96%
“…Need to maintain confidentiality [36,37] Research subjects are typically provided anonymity that may mean publication of raw data is not feasible or safe…”
Section: Challenges Of Implementing Open Synthesis and Their Relationmentioning
confidence: 99%
“…Many issues regarding the release of confidential private data of individuals can be avoided by proposing an informed consent document in which subjects approve release of their de-identified data. Requesting such permission generally has not been found to reduce the percentage of participants who enroll in the research [51,52], but if such seems likely, an opt-out for the data release can be offered, which will affect only the size of the open data set distributed.…”
Section: How To Share One's Datamentioning
confidence: 99%